Kecemasan Berbicara Bahasa Arab Siswa Program Intensif Bahasa Arab - Abdul Basith (TADRIS AL-ARABIYAT: Jurnal Kajian Ilmu Pendidikan Bahasa Arab, 2021)
Anxiety is a state of apprehension or worry that indicates that something bad will happen soon. And anxiety will turn into abnormal if the level does not match the proportions of the threat, or if it comes without any cause, that is, if not a form of response to the environment that will change. In the extreme, an anxiety will interfere with our daily activities. The aim of ths research is to know: (1) the level of theanxiety that students of arabic intensive program experienced when they speak arabic, (2) the factors that cause this anxiety when speak arabic that the students of arabic intensive programe experienced, and (3) the strategy on dealing this anxiety by the students of arabic intensive programe. This research use blended-method (qualitative and quantitative). This research is held in Unit Pelaksana Teknis (UPT) Bahasa Institut Agama Islam Darussalam (IAIDA) Blokagung Banyuwangi. The subjects of this research are the students who experienced the anxiety on speaking arabic in the arabic at UPT Bahasa IAIDA. They all are choosen by using purposive sampling. The researcher measure the level anxiety by using FLAS (Foreign Language Anxiety Scale) while observing and interviewing all of the students of arabic intensive program to identify the factor that cause the anxiety on speaking arabic. The researcher doing the observation by interviewing intensively and take field note. Intensive interview to the studens is used to know the factors of the anxiety and srudents strategy on dealing the anxiety. Meanwhile, field note is used to get the more accurate data. Based on the result found in the field, Researcher find out that the level anxiety the students have on speaking arabis is about 65% and categorized as atmedium level. While the factors that cause the anxiety on the students arabic speaking skill, in general, are divided into two categories; internal factors and external factors, and in the case of this research, the reseracher found the internal factors that are: worries on doing errors, lack of self confidence and inability to arrange the words into sentences. As for the external factors that are: the absence of supporting environment and the lack of motivation from students parrents. As for the strategy that students do, that are: preparring on learning material before entering the class and find partner in speaking arabic continously.